Employees’ Participation in Training – Comparative Characteristics and Segmented Groups - Atanasova, Margarita (Research Papers, 2010)
The constant enrichment of employees’ knowledge and skills should be analysed both in terms of effectiveness and from the perspective of the principle for ensuring a fair access and encompassing wider circles of people in varied forms of learning during employment. The problem about the relatively low levels of participation in trainings on the part of certain groups of surveyed employees is analysed in the context of the main conclusions of the theory for labour market segmentation which explains the specifics of the segmented groups. One of the key factors for the decrease in the number of these groups on the labour market is the improvement of employees’ knowledge and skills through various methods in the work process. In this respect, this survey gives special attention to analysing the differentiation of participation in trainings on the part of certain groups of employed depending on their level of education, belonging to a particular professional group, type of contractual relations with their employers, working hours and age. This study’s main purpose is to describe the participation in trainings on the part of the employed in Bulgaria against the background of these processes in the other EU Member States and the Community as a whole.In addition, special attention is given to the analysis of certain groups’ involvement in trainings, where these groups are generally characterised by low levels of participation both in formal and informal trainings: employees with elementary or lower-level education; employed in flexible types of employment and people from the high age groups.